2015
DOI: 10.15446/rfnam.v68n1.47835
|View full text |Cite
|
Sign up to set email alerts
|

Protein Quality of Rice Drinks Fortified with Bovine and Porcine Blood Plasma

Abstract: The future of nutrition in Colombia, and perhaps in other developing countries, will depend in large part on the ability of food technology to take full advantage of the food sources available in the country and to adapt and develop new products that will vary and complement the diets of the majority of the population at a low cost. The objective of this study was to evaluate the protein quality of rice-based drinks fortified with bovine and porcine blood plasma. Six treatments were prepared with different lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…The PDCAAS of whey protein is generally considered to be 1, which is the highest possible score, and its DIAAS values are even higher ( Rutherfurd et al, 2015 , Mathai et al, 2017 ). The PDCAAS score for bovine plasma-derived proteins was 78.5, although differences in protein concentrate preparation could have influenced this result ( Montero Castillo et al, 2015 ). Studies on corn protein revealed PDCAAS scores ranging from 28.7 to 67, indicating that preparation methods significantly impact protein quality ( Mendes et al, 2016 ; Zarkadas et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PDCAAS of whey protein is generally considered to be 1, which is the highest possible score, and its DIAAS values are even higher ( Rutherfurd et al, 2015 , Mathai et al, 2017 ). The PDCAAS score for bovine plasma-derived proteins was 78.5, although differences in protein concentrate preparation could have influenced this result ( Montero Castillo et al, 2015 ). Studies on corn protein revealed PDCAAS scores ranging from 28.7 to 67, indicating that preparation methods significantly impact protein quality ( Mendes et al, 2016 ; Zarkadas et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Esto ha conllevado a la búsqueda de alternativas altamente nutricionales y económicas que aporten a la población una mejor alimentación (Navarro et al, 2014;Montero et al, 2015). Sin embargo, el uso de alimentos localmente disponibles está siendo impulsado como medio de diversifica-ción dietética en la lucha contra la amenaza de las deficiencias de micronutrientes, es así, como la proteína vegetal juega un papel importante en la nutrición humana, destacando el grupo de las leguminosas, las cuales proporcionan una gama de nutrientes esenciales como proteínas, hidratos de carbono de bajo índice glicémico, fibra dietética, minerales y vitaminas (Navarro et al, 2014;Valiño et al, 2015).…”
Section: Introductionunclassified